Technology and science in the People's Republic of China : an introduction - Sigurdson, Jon (Pergamon international library of science, technology, engineering, and social studies., 1980)
Technology and Science in the People's Republic of China: An Introduction tackles several areas of concerns in the technological development of China. The title covers China's research structure, scientific resources, and technological priorities. The text first reviews contemporary China, and then proceeds to discussing Chinese history. Next, the selection talks about China's objective and policies. The text also covers the Chinese research organizations, along with education and training. Chapter 7 tackles the basic and applied science in China, while Chapter 8 details mass science. The next.